Memberikan Kognisi Melalui Pengenalan Laporan Keuangan Kepada Siswa SMK di Palembang - Mulyani Rizki (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2024)
Financial reports as a record of a company's financial information to understand this, efforts are needed to increase student awareness of the importance of financial reports as an important initiative in ensuring that students understand and are proficient in managing the financial dimensions in their personal and professional lives. Educational institutions can implement pedagogical and training programs that emphasize contemporary and effective financial reports. Obtaining the right financial literacy can equip students with the ability to understand the importance of managing finances in a broader context. The objectives of carrying out this Community Service activity are: (1) Introducing financial reports to SMK Palembang students, (2) Upholding the Tri Dharma of Higher Education at Raden Fatah State Islamic University Palembang, (3) Fostering effective cooperation between Raden Fatah State Islamic University Palembang and other stakeholders who influence the prospective progress of Raden Fatah State Islamic University Palembang. The methodology for implementing Community Service involves disseminating information to SMK Palembang students, with a total of 40 participants. The benefits obtained from this Community Service activity include: Students and educators gain a comprehensive understanding of financial reports and foster a public that has a broad perspective and knowledge of financial reports. Keywords: cognition, recognition, financial reports